AVERAGING INCOME FOR TAX PURPOSES. - Blough, Roy (The Accounting Review, 1945)
Abstract The article presents information on averaging income for tax purposes. The purpose of averaging devices is to get away from the segmentation of income into pieces one year in length or, in other words, to lengthen the accounting period for tax purposes. There is nothing very radical about this idea. Yearly income represents an aggregation of 52 weekly incomes and 12 monthly incomes. Tax accounting periods as short as one week and as long as two or three generations are conceivable and in fact, have been suggested. Although taxation is only one of several areas in which the defects of the annual income period are patent, it is perhaps the most important. In preparing income statements for most purposes, relevant facts and expectations outside or beyond the formal accounting figures can be recognized when action is to be taken or decisions are to be made. Moreover, reserves can be set up in the accounts to give a degree of formality to these facts and expectations. In the case of taxation, however, such adjustments are not feasible.